Prevalence and correlates of vibration perception threshold based diabetic peripheral neuropathy in Gujarati urban population: A cross sectional study - Jayesh D Solanki; Rishita D Doshi; Neel R Virani; Nidhi S Sheth; Jatin K Dhamecha; Chinmay J Shah (Journal of Family Medicine and Primary Care, 2022)
Background: Diabetic peripheral neuropathy (DPN) is common microvascular complication with lack of data from many regions. Vibration perception threshold (VPT) is an objective tool to screen vibration-based neuropathy both quantitatively and qualitatively. We studied prevalence that correlates VPT in diabetic sample population. Methods: A cross-sectional study was performed in 100 under treatment urban type 2 diabetics. Using bioesthesiometer, we tested VPT from sole of lower limbs of each participant. VPT >25 was considered as DPN. VPT was further correlated to determinants using t test, chi square, and multiple linear regressions. P < 0.05 was taken as statistically significant. Results: Mean age was 57, mean duration was 9.42 years, 40% were good glycemic, 28% were symptomatic for neuropathy, half subjects had co-existing hypertension and positive family history. VPT >25 was prevalent in 38% participants and mild, moderate, severe grades of DPN were present in 10%, 20%, 38%, respectively. VPT was associated with all three measures of glycemic control both quantitatively and qualitatively imposing significant odds risk (3.45, 2.63, 3.63 for HbA1C, FPG, 2hPG, respectively). Presence of symptoms, duration, and family history were significant predictors of VPT, whereas age, gender, hypertension, hyperlipidemia, and glycemic control were not. Conclusion: In chronic type 2 diabetics from a city Gujarat, we report 38% prevalence of DPN, related to symptoms, duration, family history, and all measures of glycemic triad. Unrelated to age and gender, VPT is superior to symptoms to detect DPN and it should be used optimally to insinuate timely preventive measures.